The deprivations and inequalities based on settlement typologies and urban form: the case of Addis Ababa, Ethiopia - Gelet, Gizachew Berhanu; Woldemikael, Solomon Mulugeta; Beyene, Ephrem Gebremariam; Fetene, Aramde; Tesfaw Mengistu, Daniel (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Informal settlement is the physical expression of inequalities and deprivations, as it indicates the failure of housing policy and the resultant gaps in living conditions. Based on the aforementioned grounds, the purpose of the paper is to analyze the physical extent and proportion of populations living in formal and informal settlements in Addis Ababa from 2011 to 2022. The study differentiated informal and formal settlement areas in Addis Ababa based on the slum ontology concept at the settlement level, a literature review, local contexts, and ground verification. Based on the morphology of formal and informal settlement areas in Addis Ababa, the study estimated the proportion of the population living in informal settlements for 2010 and 2020. The 2010 and 2020 informal settlement populations were extracted based on the 100-meter gridded spatial population data obtained from WorldPop. The study used the 2011 aerial photograph and the 2022 Google Earth image for interpretations and differentiations of formal and informal settlements. Then, the research analyzed the spatial extent, population level, and trends of formal and informal settlements. The major findings of the study indicated that informal areas constituted 61% and 59% of the residential land use in 2011 and 2022, respectively. In the intervening period (from 2011 to 2022), the informal and formal settlements of Addis Ababa have grown annually by 2.92% and 4.98%, respectively. In 2010, 67.9% of the population in Addis Ababa lived in informal settlements, while the population living in informal settlements was 53.8% in 2020. The deprivation areas versus population size study indicated the divided city pattern of urban inequality revealed by the concentration of a large deprived population in the inner-city slums and peri-urban areas. The findings also indicated appropriate area-based policy and planning interventions to reach large populations disproportionally deprived to bridge the gap in urban inequality.